موضوعات الأدب الصوفي في نصوص الطريقة الشيخية (Revue El-Wahat pour les Recherches et les Etudes, 2021)
A new type of literature has accompagnied the emergence of Sufism since the second century of egira wich is soufi literature. This literature has some crossroads with arabic literature in some genres. But not in the subjects treated.   This article consists on revealing the soufism subjects(divine love, divine winery, the mohammadian truth, the praise of Shoyoukh (masters) in some of the production of the Boushikhi soufi order wich was founded by Saint Abdelkader bin Mohamed well known as Sidi Sheikh who died in 1025 of Hegire. His order stretched from east Moroccan region (Figuig)to the south east of Algeria (Ain Salah) because the texts of the Boushikhi order are considered as a behavioral education to social class by its attending to religious ceremonies and popular meetings and weddings in form of songs that shakes emotions of popular class. And as a result of this barely no family was without a singer of this particular songs. Keywords –  Soufi literature, divine love, Mohammadian truth, Boushikhi order, Shoyoukh praise